OPTIMALISASI PENYELENGGARAAN PELATIHAN GUNA MENINGKATKAN KEMAMPUAN TEMPUR PRAJURIT TNI AL DALAM RANGKA MENDUKUNG PELAKSANAAN TUGAS POKOK KOMANDO ARMADA RI KAWASAN TIMUR (Studi Di Satuan Kapal Amfibi) - _, Widodo (Jurnal Ketahanan Nasional, 2014)
The aim of this was to described the combat capability that can be achieved by the Soldiers of the Navy, training events that had been implemented to enhanced the combat capability of Navy Soldiers, and efforted to optimized the implementation of training to improved the combat capability of the Navy in Amphibious Ship Unit Soldiers Koarmatim. Based on the objectives to be achieved, so the research applied the naturalistic qualitative approach by using data collection method which involved: participant observation, in-depth interviews and document search. Technical Data analysis using qualitative descriptive techniques through three lanes of activities, include; reduction, data display and conclusion. The obtained fi ndings could be described as followed. First, Mastery of navy soldier combat capability of Eastern Fleet Command Amphibious Warship Unit Koarmatim demonstrated achievement of combat capability with sufficient skilled category. Second, The refinement of pattern, method and training organization . Third, in the implementation of training, there were still barriers.Keywords: Optimization, Training Implementation, Combat Capability